Cord blood innate-like T cell responses in neonates born to healthy women and women living with HIV - Rach, David; Hsu, Hao-Ting; Nampota-Nkomba, Nginache; Mvula, Godfrey; Mkandawire, Felix A.; Nyirenda, Osward M.; Hritzo, Bernadette; Boldrin, Francesca; Degiacomi, Giulia; Mazzabò, Laura Cioetto; Manganelli, Riccardo; Buchwald, Andrea G.; et al. (Frontiers in Immunology, 2025)
Innate-like T cells (ILT), including γδ T cells (Vδ2s), Natural Killer T cells (NKTs) and Mucosal-associated Invariant T cells (MAITs), integrate innate and adaptive immunity, playing important roles in homeostatic conditions as well as during infection or inflammation. ILT are present on both sides of the fetal-maternal interface, but our knowledge of their phenotypical and functional features in neonates is limited. Using spectral flow cytometry we characterized cord blood ILT in neonates born to healthy women and women living with HIV. We describe extensive phenotypic and functional heterogeneity within the cord Vδ2 cells at baseline and following activation. In neonates born to women with HIV, we observed modest differences in ILT frequencies ex-vivo and altered proportions of Vδ2 cells producing IFNγ+ or TNFα+, both ex-vivo and after expansion, compared to HIV unexposed infants. Consistent with prior studies, infants born to mothers who initiated ART before pregnancy exhibited less immune perturbation overall. Herein we expand our knowledge of ILT at the maternal-fetal interface by a comprehensive phenotypic analysis of these rare subsets.